The impact of Brexit on the member states’ ability to build blocking coalitions in the Council - Kleinowski, Marcin (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
Using a proprietary computer program, simulations of voting in the Council after Great Britain’s withdrawal from the EU were carried out. In the case of some of them, a methodological innovation consisting in departing from the assumption that the emergence of each possible coalition is equally probable was used. The analysis conducted indicates that after Brexit the ability of the Council members to form small minimally blocking coalitions will change significantly. At the same time, the assessment of the ability of states to block decisions in the Council and made on the basis of the Preventive Power Index, differs fundamentally from the results of the analysis focusing on building small minimally blocking coalitions. This research is funded by the National Science Centre, Poland, under project no. UMO-2016/23/D/HS5/00408 (SONATA 12 grant) entitled “The Impact of Brexit and Unconditional Introduction of the ‘Double Majority’ Voting System on Decision- Making in the Council of the European Union.”

Przy wykorzystaniu autorskiego programu komputerowego wykonano symulacje głosowań w Radzie po wystąpieniu Wielkiej Brytanii z UE. W przypadku części z nich zastosowano innowację metodologiczną polegającą na odejściu od założenia, że powstanie każdej z możliwych koalicji jest równie prawdopodobne. Przeprowadzona analiza wskazuje, że po Brexicie znacząco zmieni się zdolność członków Rady do tworzenia małych koalicji minimalnie blokujących. Jednocześnie ocena zdolności państw do blokowania decyzji w Radzie, dokonana w oparciu o Preventive Power Index, różni się zasadniczo od wyników analizy skupiającej się na budowie małych koalicji minimalnie blokujących. Prezentowane badania zostały sfinansowane przez Narodowe Centrum Nauki w ramach projektu no. UMO-2016/23/D/HS5/00408 (konkurs SONATA 12) zatytułowanego Wpływ brexitu i bezwarunkowego wprowadzenia systemu głosowania „podwójną większością” na proces decyzyjny w Radzie Unii Europejskiej.
Wpływ Brexitu na zdolność państw członkowskich UE do budowania koalicji w Radzie
Keywords: Brexit; blocking coalitions; Council of the European Union; voting power; Brexit; koalicje blokujące; Rada Unii Europejskiej; siła głosu